AGRIBISNIS PERKEBUNAN RAKYAT KOPI ROBUSTA DI KABUPATEN SOLOK - Hariance, Rika; Febriamansyah, Rudi; Tanjung, Faidil (Jurnal AGRISEP, 2015)
The largest area of local coffee plantation in West Sumatera Province is in the District of Solok, that covers the area around 9,300 Ha, with the annual production of 8,500 Ton. There are two varieties of coffee in this District, arabica and robusta. The area of robusta coffee is around 7,700 Ha that are much larger than arabica of 1,600 Ha. Although the price of arabica coffee is much higher than robusta, farmers prefer to cultivate robusta coffee mainly due to its resistance to plant diseases, low maintenance cost and higher demand compare to arabica coffee. Since the Robusta coffee is the second largest of local plantation after casiavera in Solok. There is a need for the district government to get a suitable development not only for the benefit of local farmers but also for regional development of Solok district itself. This study applied descriptif qualitative method to analyze the interrelationship of agribusiness sub-systems and its potential aspect. The results shows that the interrelationship of four subsystems of the agribusiness of Robusta coffee agribusiness were not strong enough to face the influences from the external factors of the systems. This, then guided the recommendation to improve the competitiveness of the Robusta coffee, mainly by increasing the quality and appearance of its market form and its dairy products.